Capital in illegal online drug markets: How digital capital changes the cultural environment of drug dealing - Bakken, Silje Anderdal (Theoretical criminology, 2023)
Digital societies demand technological competence, including for actors in illegal activity. Inspired by Bourdieu’s theory of cultural capital and related criminological concepts such as street capital, this study analyses digital capital as a wider concept relating to digital drug markets that capture both technological and cultural competences. We pursue this empirically via interview data (N = 107) on social media and darknet drug markets. The overall need for digital competence erodes the earlier divide in drug markets based on either subculture or networks. The need to be familiar with mainstream technological tools and behaviours connects digital drug markets to more general cultural competencies. Consequently, illegal activities become connected with mainstream cultural capital because both fields value the same competencies.